Incitement Against Authority Between Enmity and Conflict as Representation of Classical Malay Literature - Syaifuddin (Talenta Publisher, 2026)
The book Critical Approaches to Literature by David Daiches, which has been widely used as a reference by scholars of both Eastern and Western literature, emphasizes the complexity of fully appreciating a literary work. The characteristics of Sejarah Melayu and Hikayat Deli as classical Malay literary works justify their classification as narrative hikayat texts. The aims of this analysis is showing the comprehending as a way to deliver information about an event on a cultural context which is regarding as a specific work perceived as distinct from other literary forms.The research problem concerns the meanings and interpretations of the narrative elements of incitement, authority, enmity, and conflict in Sejarah Melayu and Hikayat Deli as literary works, which are often appreciated merely for their aesthetic language. The approach employed adopts the author’s narrative perspective within the framework of postmodernist thought.The findings indicate that the construction of incitement follows particular patterns directed toward authority, representing a reality of enmity and conflict shaped through narrative imagination.